Exposure and response prevention therapy augmented with naltrexone in kleptomania: a controlled case study using galvanic skin response for monitoring. Issue 5 (21st March 2019) - Olbrich, Sebastian; Jahn, Ina; Stengler, Katarina
Abstract: Background: Kleptomania is a disease that shares features with obsessive compulsive spectrum disorders (OCD) and with substance abuse disorders (SAD). This is underlined by therapeutic approaches in kleptomania ranging from cognitive behavioural therapy and selective serotonin reuptake inhibitors that are effective in OCD, and opioid antagonists that are currently being used in SAD. However, almost no literature exists about exposure and response prevention (ERP) therapy in kleptomania. Furthermore, there is a clear lack of objective markers that would allow a therapeutic monitoring. Aim: To show the effectiveness of ERP therapy in kleptomania in a single case report. Method: An ERP therapy under real-world conditions and later augmentation with the opioid antagonist naltrexone is described. Continuous measurements of galvanic skin response (GSR) before, during and after therapy sessions are reported in association with changes of the Kleptomania Symptom Assessment Scale (KSAS) self-questionnaire. Results: While KSAS scores showed a clear treatment response to ERP sessions, the GSR was significantly lower during ERP treatment in comparison with baseline measures. However, during augmentation with naltrexone, GSR measures increased again and clinical severity did not further improve. Conclusions: This case shows the possible usefulness of ERP-like approaches and therapy monitoring using electrophysiological markers of arousal for individualized treatment in kleptomania.